WOMEN FISH VENDORS IN THOOTHUKUDI: A STUDY OF THEIR MARKETING AND DISTRIBUTION APPROACHES - Sony, Ms. O. Sony; Jeyakumari, M. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Women merchants in the fish market transcend mere business ownership; they embody a distinct identity. Their ascent to brand recognition is characterized by a commitment to excellence, a personalized approach, and a focus to fostering robust, enduring connections with the people they serve. This study aims to examine and evaluate the marketing and distribution strategies utilized by these female sellers, highlighting the challenges they face and the creative methods they choose to maintain their livelihoods. Comprehending these aspects is crucial for formulating targeted interventions to enhance the economic empowerment of women in the fish selling sector.